Dynamic Optimization for Fast Image Transfer and Visualization for Mobile and Stationary Devices: A Performance Evaluation Using Animati Viewer - Venson, José Eduardo; Bevilacqua, Fernando; Maia, Carlos Edmilson; d'Ornellas, Marcos (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS); 2015: Anais do XV Workshop de Informática MédicaDO - 10.5753/sbcas.2015.10376, 2015)
medical application running outside the workstation environment has to deal with several limitations, such as reduced available memory and low network bandwidth. Adaptations and novel approaches are required to make applications overcome such problems. This paper presents an approach that uses a combination of client- and server-side procedures to dynamically optimize the data flow for fast image transfer and visualization on mobile and stationary devices. The main goal of our approach is to minimize the amount of data transferred to and used in the host device without sacrificing the user experience. Our approach was implemented and validated using a real use case, the application Animati Viewer, which is a web visualizer for diagnostic images. The evaluation was measured using metrics such as the accumulated amount of network transferred data and the amount of memory used in the host device. The results show that our approach is feasible and, in one of our tests, it transferred only 7.73% of the amount of data downloaded by the OsiriX mobile.